ANALISIS PROGRAM CORPORATE SOCIAL MARKETING, PENGETAHUAN KONSUMEN DAN REPUTASI PERUSAHAAAN DALAM MENCIPTAKAN GREEN CONSUMERISM (PROGRAM TUMBLER STARBUCK ON THE GO) - Devina Susilo (Institute of Research and Community Outreach - Petra Christian University, 2014)
The study aimed to clarify the influence of corporate social marketing programs on consumer knowledge and reputation of the company in creating green behavior Consumerism. The study was conducted to consumers of Starbucks Coffee, in an explanatory study with a sample size of 200 respondents. The analysis was performed descriptively and kausalistik in the form of structural equation models. The findings of this study is that the implementation of corporate social marketing program has a positive impact on consumer knowledge and the company's reputation as a green company. CSM program can create and educate consumers and then engaged consume products more responsibly towards the environment, and ultimately promote the creation of green Consumerism.